Coupled water–carbon flux processes of date palms under lysimeter-based saline irrigation: CoupModel calibration and evaluation - Jingbo Zhen; Per-Erik Jansson; Effi Tripler; Xiaotao Hu; Naftali Lazarovitch (Agricultural Water Management)
Date palms are a cash crop and commonly irrigated using saline water. A better understanding of the processes involved in water use by date palms and their carbon budget is key to sustainable cultivation and saline irrigation scheduling. In this study, the process-oriented CoupModel was used to investigate the linked water and carbon fluxes in date palms under saline irrigation conditions. We compared experimental data for actual evapotranspiration (ETc act) and yield from trees grown in weighing lysimeters and irrigated at two salinity levels in 2006–2007 with an uncertainty-based calibration approach. The daily ETc act and annual yield of trees with the low-salinity irrigation in 2006 were used to calibrate the selected parameters, investigate model performance, and analyze parameter correlations. Further tests were undertaken, including the application of low-salinity irrigation in 2007 and high-salinity irrigation over two years. Dynamic modeling of the tree canopy and a radiation use efficiency approach, along with incorporating the salinity effects on plant respiration and consideration of internal water storage, accurately simulated the measured data. The model determined the direct responses of the date palms to varying irrigation water amounts and salinity, and atmospheric conditions. It robustly determined the characteristics of daily ETc act and annual yield for both irrigation salinities in each year. Based on the selected parameterization, the daily ETc act was accurately simulated for both irrigation salinities in each year. However, the yield was only accurately simulated for both irrigation salinities in 2006. In addition, the simulated amounts and calculated electrical conductivity of daily drainage water suggested that the model performed well in simulating the soil water and salinity conditions, particularly during the fruit growing season. In general, the lysimeter-based parameterization of the CoupModel applied to inter-yearly growth of palms under saline irrigation conditions helps long-term continuous simulations and agronomic applications.